(untitled) (River Edge, NJ., 2003)
The Sixth International Workshop on Complex Structures and Vector Fields was a continuation of the previous five workshops (1992, 1994, 1996, 1998, 2000) on similar research projects. This series of workshops aims at higher achievements in studies of new research subjects. The present volume will meet with the satisfaction of many readers.
Keywords: Functional analysis,Geometry, Differential,Mathematical physics